2022
DOI: 10.3390/jcm11113158
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Update Findings about pH-Impedance Monitoring Features in Laryngopharyngeal Reflux Patients

Abstract: Purpose: The diagnosis of laryngopharyngeal reflux (LPR) is commonly based on non-specific symptoms and findings and a positive response to an empirical therapeutic trial. The therapeutic response is, however, unpredictable, and many patients need pH-impedance monitoring to confirm the diagnosis. Methods: A review of the recent literature was conducted in PubMED, Scopus, and Embase about the pH-study features of LPR patients. A summary of last evidence was proposed. Results: The awareness of otolaryngologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 84 publications
0
30
0
Order By: Relevance
“…LPR is considered as a silent reflux, without significant correlation between pharyngeal reflux events and symptoms at the HEMII‐pH. 29 In other words, the inflammatory reaction of laryngopharyngeal mucosa required a few weeks of backflow of gastroduodenal content into the upper aerodigestive tract, 30 , 31 which supports that LPR symptoms develop a few weeks after the surgery. In most studies, authors assessed LPR symptoms and findings at least 6 weeks postthyroidectomy, which seems adequate.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…LPR is considered as a silent reflux, without significant correlation between pharyngeal reflux events and symptoms at the HEMII‐pH. 29 In other words, the inflammatory reaction of laryngopharyngeal mucosa required a few weeks of backflow of gastroduodenal content into the upper aerodigestive tract, 30 , 31 which supports that LPR symptoms develop a few weeks after the surgery. In most studies, authors assessed LPR symptoms and findings at least 6 weeks postthyroidectomy, which seems adequate.…”
Section: Discussionmentioning
confidence: 95%
“…The importance of HEMII‐pH is strengthened by the nonspecificity of LPR symptoms and findings (e.g., globus sensation, throat clearing, dysphagia, dysphonia), which may be commonly found in patients with laryngeal nerve injury without reflux. Scerrino et al 15 used esophageal pH‐monitoring to investigate esophageal proximal events, but, in practice, we know that many esophageal reflux episodes do not reach pharynx because UES tonicity 29 . From an epidemiological standpoint, the nonspecificity of LPR‐symptoms and findings may support the careful exclusion of comorbidities that may be associated with laryngopharyngeal symptoms 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 52 The low efficacy of PPIs is related to the high prevalence of weakly acid and non-acid (alkaline) LPR, which require treatment with alginate or magaldrate. 53 , 54 …”
Section: Therapeutic Outcomesmentioning
confidence: 99%
“…52 The low efficacy of PPIs is related to the high prevalence of weakly acid and non-acid (alkaline) LPR, which require treatment with alginate or magaldrate. 53,54 According to data in the the literature, elderly LPR patients report different therapeutic responses from younger patients. [44][45][46] Lee et al reported significantly more responders to PPI therapy, defined as those whose RSI score improved by more than 50%, in both the 18-39-year-old group (86%) and the 40-59-year-old group (75%), compared with the >60-year-old group (57%).…”
Section: Therapeutic Outcomesmentioning
confidence: 99%